ANALISIS INDEKS KEPUASAN MASYARAKAT (IKM) DALAM PENERIMAAN PELAYANAN ADMINISTRATIF DI KANTOR CAMAT TAMPAN KOTA PEKANBARU - Amanda Dwi Putri; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Analysis Of Community Satisfaction Index In Receipt Of Administrative Services At The District Tampan Office Pekanbaru. This study aims to determine how the Community Satisfaction Index in receipt of services and what are the factors that influence people's satisfaction Tampan District Office in the city of Pekanbaru. The method used in this study is a quantitative and qualitative research method. Researchers using accidental sampling technique (by chance) To meet the accuracy of indexing, set at a minimum of 150 respondents was selected out of a population of service recipients. Data collection was conducted by means of questionnaires, interviews, and observations. In this study indicators of community satisfaction refers to the Decree of the Minister of State for Administrative Reform Number : Kep/25/M.PAN/2/2004 on Guidelines for Preparation General Public Satisfaction Index Services Unit Government Agencies, and the factors that influence people's satisfaction of the writer grab theory of management service by Ratminto. The results showed that the Customer Satisfaction Index in receipt of services in the city of Pekanbaru categorized District Office has been good with the value 77.6 (Good). While the factors that affect people's satisfaction at Tampan Head Office is the organization's culture, systems services, human resources and service users.Key words: Public service, quality of service, community satisfaction